Vergleich der Variabilität im Nordatlantik in Klimasimulationen mit und ohne Flusskorrektur - Jacksohn, Christoph (2018)
Many climate models exhibit biases in the North Atlantic, especially a too cold sea surface temperature (SST) and a false track and strength of the ocean circulations compared to observed data. For the Kiel Climate Model (KCM), Park et al. (2016) have shown that those biases can be reduced by the implementation of a freshwater flux correction. The freshwater flux correction leads to a fortification of the Atlantic Meridional Overturning Circulation (AMOC), most notably in its decadal and multi-decadal variability. Moreover, it strengthens the interaction between the North Atlantic Oscillation (NAO), which has decisive impact on the internal variability of the North Atlantic climate, and the AMOC. In other studies, the impact of the atmosphere and the ocean on each other in relation to the NAO has primarily been shown for the sub-decadal variability of the NAO. Therefore, in this thesis the two model experiments with and without freshwater flux correction compared by Park et al. (2016) are analysed with regard to the impact of the freshwater flux correction in KCM on the subdecadal NAO variability. To this end, the spectrums of the NAO in both experiments are analysed and lag-regressions of multiple parameters are performed on the reconstructions of the dominant NAO modes, identified by a Singular Spectrum Analysis (SSA). The freshwater flux correction induces a fortification of the interaction between the ocean and the sub-decadal NAO variability. This occurs on higher frequencies with periods of 5 years instead of 8 years in the uncorrected experiment. Especially the movement of the sub polar deep convection site from the south end of Greenland in to the Labrador Sea that has been shown by Park et al. (2016) seems to have a substantial impact on these findings, e.g. the movement of the heat flux anomalies in the same region. However, this connection could not be proven definitely with the parameters analysed and the methods used in this thesis. Thus, it is necessary to conduct further investigations using ...